Defining response and nonresponse to posttraumatic stress disorder treatments: A systematic review. Issue 4 (11th July 2020) - Varker, Tracey; Kartal, Dzenana; Watson, Loretta; Freijah, Isabella; O'Donnell, Meaghan; Forbes, David; Phelps, Andrea; Hopwood, Malcolm; McFarlane, Alexander; Cooper, John; Wade, Darryl; Bryant, Richard; et al.
Abstract: There is currently no uniform definition of treatment response for posttraumatic stress disorder (PTSD) to guide researchers and clinicians in the area of posttraumatic mental health. The aim of this systematic review was to explore the operationalization of PTSD treatment response, by reviewing and synthesizing the key criteria used to define treatment response and treatment nonresponse in published trials. Randomized controlled trials (RCTs) assessing the effectiveness of first‐line interventions for PTSD were identified for inclusion. Of those, 143 trials provided 226 definitions of treatment response, grouped under five main categories: treatment response ( n =  181), remission ( n  = 23), recovery ( n  = 5), treatment nonresponse ( n  = 5), and worsening ( n  = 12). Overall, the results showed the PTSD field utilizes diverse and interchangeable operational definitions of treatment response and nonresponse, indicating a need for more precise conceptual definitions and operational criteria. A set of operational research definitions are presented in order to advance the PTSD treatment field.